Penerapan Arsitektur Bisnis Intelijen dalam Strategi Bisnis Penjualan setelah Pandemi Covid-19 - Devia Naomira, Allysa; Fauzi, Achmad; Puspita Sari, Dewi; Azhari, Farhan; Salsabilla, Luthfia; Khadir Ali, Muhammad; Astriyani, Rini; Arisana, Vina (Dinasti Review Publisher, 2023)
The purpose of this study is to analyze sales promotion initiatives with online media after the Covid-19 pandemic. This journal is written using qualitative methods. This research was obtained by collecting information or theory from the literature on Google Scholar online journal articles related to this article. The focus of the study of this research is to create an online sales strategy amid the Covid-19 pandemic. The results of this study are the impact of the Covid-19 pandemic on sales, the development of online shopping during the Covid-19 period, and an analysis of sales strategies using online media after the Covid-19 pandemic, what is the marketing strategy. products during a pandemic on social media and how to target loyal customers.